The impact of COVID-19 on agricultural trade, economic activity, and poverty in Africa - Bouët, Antoine; Laborde Debucquet, David; Seck, Abdoulaye (AKADEMIYA2063, 2021)
This chapter reviews efforts to estimate the impact of the COVID-19 pandemic on agricultural trade, economic activity, and poverty in Africa, in view of the critical role that agricultural trade plays for millions of poor people. The next section presents the responses to the pandemic. The following one introduces the channels through which the pandemic affected African agricultural trade. Then the penultimate section assesses the impact of the crisis. The final section concludes.